An analysis of the heavy element distribution in edible tissues of the swimming crab (Portunus trituberculatus) from Shandong Province, China and its human consumption risk. (August 2021) - Yang, Luping; Wang, Dejun; Xin, Chenglong; Wang, Lin; Ren, Xiaofei; Guo, Mingcai; Liu, Yongjun
Abstract: This study evaluated the food safety of the swimming crab ( Portunus trituberculatus ) found in Shandong Province, China and obtained information on possible edible parts and gender differences. White and brown muscle samples from 108 swimming crabs were collected from seven cities along the eastern coastline of Shandong Province and analyzed for levels of Cu, Zn, Ni, As, Fe, Mn, Cr, Se, Cd, and Pb. There were significant differences in the metal concentrations among different edible muscles. High concentrations of Zn, Mn, and Cr were found in leg and claw meat while Fe, Cu, Ni, As, Cd, Pb, and Se were predominantly found in the hepatopancreas and gonads. Gender differences were found only for Fe and Zn. Based on the estimated daily intake (EDI), target hazard quotient (THQ), total target hazard quotient (TTHQ), and the permissible safety limits prescribed by various agencies, consumption of the swimming crab is considered safe. Graphical abstract: Unlabelled Image Highlights: Highest concentrations of Zn, Mn, and Cr were in the leg and claw meat. The hepatopancreas and gonads had the highest levels of Fe, Cu, Ni, As, Se, Cd, and Pb. Except for Fe and Zn, the metal concentration does not depend on the gender of the crab. Consumption of brown meat is a potential health risk due to high Cd levels. Values were within safe limits except for As, which is of less health concern.